Bio-templated bioactive glass particles with hierarchical macro-nano porous structure and drug delivery capability - Zheng, Kai; Bortuzzo, Judith Agnes; Liu, Yufang; Li, Wei; Pischetsrieder, Monika; Roether, Judith; Lu, Miao; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2014)
Hierarchically porous bioactive glass particles (BGPs) were synthesized by a facile sol-gel process using pollen grains as the templates. The synthesized pollen-templated bioactive glass particles (PBGPs) exhibited dual macro-nano porous structure. The macro pores ( 1μm) were inherited from the template of pollen grains while the nano pores ( 9.5nm) were induced by the intrinsic mechanism of the sol-gel process. PBGPs possessed a high specific surface area (111.4m/g) and pore volume (0.35cm/g). Hydroxyapatite (HA) formation on PBGPs was detected within 3 days after immersion in simulated body fluid (SBF). Due to their larger specific surface area and pore volume, PBGPs could be loaded with more tetracycline hydrochloride (TCH) than non-templated BGPs and conventional melt-derived 45S5 BGPs. In addition, PBGPs exhibited a low initial burst release (within 10% of the loaded amount) within 18h and a sustained release with a two-stage release pattern for up to 6 days in phosphate buffered saline (PBS). The antibacterial assay confirmed that the TCH-loaded PBGPs could release TCH within 5 days, and the released TCH could reach the minimum inhibitory concentration (MIC) against Escherichia coli. MTT assay indicated that PBGPs showed non-cytotoxic effects toward human hepatocellular carcinoma (Hep G2) cells after co-culture for up to 72h in vitro. These results showed that the biocompatible hierarchically macro-nano porous PBGPs are potential for bone regeneration and local drug delivery applications.
Keywords: Bio-template; Bioactive glass; Drug delivery; Hierarchical pores